2017
DOI: 10.1021/acs.jpcc.7b02915
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Porous Graphenes for Alkane Isomer Separation

Abstract: Using first-principles calculations, we systematically evaluated a series of single-layer porous graphene membranes with different sized pores passivated by hydrogen atoms for separating short alkane isomers (C = 5–7). We found that graphene membranes with appropriate pore size (e.g., the pore19 model whose pore size is 8.0 × 5.8 Å) could efficiently separate dibranched isomers from their monobranched and linear counterparts. When alkane molecules diffused through a membrane, the porous graphene might exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Several theoretical and computational studies have focused on elucidating transport of gases, ions, and molecules across nanoscale pores in 2D materials for membrane applications, and experimental studies are rapidly emerging . Here, we focus on i) the mechanisms of transport in 2D material membranes, ii) summarize experimental advances in realizing atomically thin membranes, and iii) discuss technological opportunities and challenges to enable applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical and computational studies have focused on elucidating transport of gases, ions, and molecules across nanoscale pores in 2D materials for membrane applications, and experimental studies are rapidly emerging . Here, we focus on i) the mechanisms of transport in 2D material membranes, ii) summarize experimental advances in realizing atomically thin membranes, and iii) discuss technological opportunities and challenges to enable applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, it was demonstrated that the graphene sheet with nanometer-sized pores (nanoporous graphene, NPG) was a very promising gas separation membrane, owing to its atomic thickness, , good chemical stability, , and high mechanical strength. , Because of the one-atomic thickness and the subnanometer pore size, the permeability and selectivity of NPG membranes can exceed those of conventional polymer gas separation membranes by several orders of magnitude. Encouraged by the great potential of NPG membranes, more and more researchers have devoted themselves to the related studies, and the NPG-based gas separation membranes are becoming a reality under the efforts of scientists.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Defects in the membrane can also induce a decrease in barrier height, and a study by Bhatia et al predicted that Ofunctionalized defective nanoporous graphene membranes could yield high values of selectivity and permeance. 24 An industrially acceptable selective transmission of 3 He was theoretically predicted for a recently synthesized porous carbon nitride membrane under moderate tensile strength. 20 While all of these studies considered the mass dependence of tunneling effects, they neglected the contribution from the zero-point energy (ZPE).…”
Section: ■ Introductionmentioning
confidence: 97%
“…22−25 The isotope separation capabilities of various carbon allotropes like graphdiyne and graphenylene showed higher transmission rates and selectivities compared to the poly(phenylene) network due to their optimal pore configurations. 17,26 In the case of nanoporous graphene, on moving from a double-ring hydrogen-passivated pore to a double-ring nitrogen-passivated pore, the barrier height was found to decrease considerably allowing a higher transmission of 3 He by quantum tunneling. 22,23 Defects in the membrane can also induce a decrease in barrier height, and a study by Bhatia et al predicted that Ofunctionalized defective nanoporous graphene membranes could yield high values of selectivity and permeance.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation